1991
DOI: 10.1007/bf00368193
|View full text |Cite
|
Sign up to set email alerts
|

Experimental bacterial prostatitis in rats

Abstract: Experimental acute bacterial prostatitis in rats was induced by four different routes of bacterial inoculation. The most simple and reproducible method of producing bacterial prostatitis was to instil the bacterial suspension into the prostatic urethra after the administration of an appropriate antibiotic to prevent associated pyelonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…Microorganisms gain access to renal tubules by a calicotubular reflux or via the blood or lymphatic vessels. This most likely correlates, as stated before, with a relatively higher incidence of prostate and bladder changes in males (Goto et al 1991) and is also observed experimentally. This was attributed to ureter obstruction since, if released soon after being created, the consequences are alleviated (Claesson et al 1987).…”
Section: Biologic Featuressupporting
confidence: 85%
“…Microorganisms gain access to renal tubules by a calicotubular reflux or via the blood or lymphatic vessels. This most likely correlates, as stated before, with a relatively higher incidence of prostate and bladder changes in males (Goto et al 1991) and is also observed experimentally. This was attributed to ureter obstruction since, if released soon after being created, the consequences are alleviated (Claesson et al 1987).…”
Section: Biologic Featuressupporting
confidence: 85%
“…Experimental chronic bacterial prostatitis was induced by the instillation of a bacterial suspension ( Escherichia coli , 10 8 colony-forming units [CFU]/mL) into the prostatic urethra. Previous studies have suggested that intraurethral inoculation is the best method of producing bacterial prostatitis in rats [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Інфекційні агенти потрапляють до передміхурової залози гематогенним та лімфогенним шляхами або через систему вивідних протоків залози з уретрального каналу, а також ретроградно через рефлюкси з сечового міхура (Johnston, Kamolpatana, Root-Kustritz, & Johnston, 2000;Tsvetkov, Makarova, & Mkhytarov, 2013 (Nickel еt al., 1990) та відтворена (Goto et al, 1991).…”
Section: сумской национальный аграрный университет сумы украинаunclassified